2021
DOI: 10.1016/j.apergo.2020.103174
|View full text |Cite
|
Sign up to set email alerts
|

Implementing spring-foam technology to design a lightweight and comfortable aircraft seat-pan

Abstract: This paper investigates whether spring-foam technology in an aircraft seatpan can reduce weight and at the same time provides equal or better comfort. Firstly, through literature studies and iterative design process a prototype seatpan was designed and developed using spring-foam technology. This was then tested against standard aircraft seat pan for comfort and discomfort; 22 participants were asked to sit in each seat for 90 minutes while filling out comfort and discomfort questionnaire every 15 minutes. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It could be that the short duration of the test did not allow to find the differentiation between comfort and discomfort. Dangal et al [ 11 ] found differences between effects of a seat on comfort and discomfort while sitting for 90 minutes. Therefore, further study is needed with longer durations to show the effect of time in this restricted space.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that the short duration of the test did not allow to find the differentiation between comfort and discomfort. Dangal et al [ 11 ] found differences between effects of a seat on comfort and discomfort while sitting for 90 minutes. Therefore, further study is needed with longer durations to show the effect of time in this restricted space.…”
Section: Discussionmentioning
confidence: 99%
“…As in the automotive seat industry, comfort has been an important factor for passengers in choosing an airline and the aircraft for many years, and it makes sense to design a comfortable interior and seat to attract passengers. Some studies show that a seat pan design using spring-foam technology can be lighter and more comfortable than conventional foam cushion materials [60,65]. Comfort is established by six factors: anthropometry, climate, sound, vibration, illumination, and smell.…”
Section: Transportation Vehicle Seatsmentioning
confidence: 99%
“…Foam materials have been formulated from basic materials comprising polymers, ceramics and metals such as aluminum, copper, steel, titanium and even gold. This kind of material has been utilized to solve different engineering problems mainly in general structural optimization (Gibson and Ashby, 1997), ships design (Banhart et al, 1998), aerospace applications (Dangal et al, 2021;Marx et al, 2020) and automotive industry (Moon et al, 2019;Romero et al, 2021;Yavuz et al, 2016). Porous structures can be used in ballistics for military areas (Ahmadi et al, 2020;Kaboglu et al, 2018;Marx et al, 2019), shock absorbers and heat exchangers for vehicles (Chin et al, 2022;Fiedler et al, 2021;Kuruneru et al, 2020).…”
Section: Introductionmentioning
confidence: 99%